The Effect of Operational Risks for Digital Banking Services at Banks - Laksana, Rio Dhani; Shaferi, Intan; Naznii, Humaira (Jurnal Manajemen Bisnis, 2023)
Research aims: This research aims to analyze active digital banking users' perceptions of bank operational risks in providing digital banking services.Design/Methodology/Approach: This research design used a quantitative approach. The population in this study was banking customers who used Internet banking services. The sample taken in this study was 240 respondents from banks in the Banyumas Regency, Central Java, Indonesia. The method performed was purposive sampling. It used five banking risk management indicators.Research findings: Most people in the Banyumas region did not agree that Internet banking had high operational risks. As such, banks need to look at other operational risks, such as service disruptions, outsourcing failures, and internal fraud.Theoretical contribution/Originality: The Technology Acceptance Model (TAM) is an information system theory that models of how users want to accept and use technology. This model proposes that when users are offered a new system, several factors influence their decision about how and when to use the system, especially regarding the usefulness, ease of use, and external factors on beliefs, attitudes, and purpose of use.Practitioners/Policy implications: This research implemented digital banking and customer perceptions of bank operational risks in providing digital banking services because they are essential for understanding the digital banking industry. Research limitations/Implications: This study only used five indicators of banking operational risks, consisting of process, human, system, external, and legal. Other aspects, such as financial, marketing, and others, have yet to be included in this banking risk research indicator. For further research, it is suggested to add research variables, not only focusing on Internet banking applications but also on other digital banking products, such as mobile banking, phone banking, and SMS banking.